2020
DOI: 10.1080/26415275.2020.1848432
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mineral trioxide aggregate on osteo/odontogenic potential of mesenchymal stem cells: a comprehensive and systematic literature review

Abstract: The significance of dental materials in dentin-pulp complex tissue engineering is undeniable. The mechanical properties and bioactivity of mineral trioxide aggregate (MTA) make it a promising biomaterial for future stem cell-based endodontic therapies. There are numerous in vitro studies suggesting the low cytotoxicity of MTA towards various types of cells. Moreover, it has been shown that MTA can enhance mesenchymal stem cells' (MSCs) osteo/odontogenic ability. According to the preferred reporting items for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…Among root canal filling materials, investigators have widely reported the successful application of mineral trioxide aggregate (MTA) in vital pulp therapy [ 16 ]. Moreover, bioactivity and cytotoxicity measurements revealed that MTA not only shows biocompatibility toward bone marrow and dental-derived mesenchymal stem cells but also can induce their proliferation and osteo/odontoblast-like differentiation in a concentration-dependent manner [ 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among root canal filling materials, investigators have widely reported the successful application of mineral trioxide aggregate (MTA) in vital pulp therapy [ 16 ]. Moreover, bioactivity and cytotoxicity measurements revealed that MTA not only shows biocompatibility toward bone marrow and dental-derived mesenchymal stem cells but also can induce their proliferation and osteo/odontoblast-like differentiation in a concentration-dependent manner [ 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…TheraCal PT ® was the least performing tested material in the present study and is in alignment with previous studies, which proved MTA and Biodentine™ had superior regenerative powers when compared to TheraCal LC ® (Farsi et al, 2018;Kang, 2020;Manaspon et al, 2021;Omidi et al, 2020). This was further supported by Babaki et al (2020) who concluded that MTA is promising with regard to stem-cell-based endodontic approaches due to its osteo/odontogenic differentiation-inducing properties, but further animal/human trials were deemed necessary. Despite TheraCal PT ® showing superior properties to TheraCal LC ® (Sanz et al, 2021), it seems that the TheraCal family of pulp-capping agents failed to outperform other materials as shown in the present study.…”
Section: Pcr Resultsmentioning
confidence: 90%
“…An ideal pulp capping material should prevent bacterial infiltration, trigger minimal inflammation, and induce dentin bridge formation (Qureshi et al, 2014 ). Current materials clinically used for pulp capping can be generally divided into calcium hydroxide (Ca(OH) 2 ) (Peng et al, 2022 ; Whitehouse et al, 2021 ; Youssef et al, 2019 ), mineral trioxide aggregate (MTA) (Babaki et al, 2020 ; Youssef et al, 2019 ), calcium silicate (Kang, 2020 ; Kim et al, 2021 ; Onay et al 2018 ), and adhesive‐based materials (Giraud et al, 2019 ). Interestingly, MTA and calcium silicate‐based materials have a comparable effect on dentin bridge formation, inflammatory response, and success rate (Babaki et al, 2020 ; Paula et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various MTA materials were tested on bone marrow-derived MSCs and were demonstrated to be non-toxic, but they could affect tooth-derived stem cells in a concentration and time-dependent manner [18]. Studies indicate that MTA materials can promote the proliferation and survival of MSCs derived from dental tissues including apical papilla, exfoliated deciduous teeth, and dental pulp [19].…”
Section: Discussionmentioning
confidence: 99%